Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1007/s10461-021-03296-8
|View full text |Cite
|
Sign up to set email alerts
|

Changing Knowledge and Attitudes Towards HIV Treatment-as-Prevention and “Undetectable = Untransmittable”: A Systematic Review

Abstract: People on HIV treatment with undetectable virus cannot transmit HIV sexually (Undetectable = Untransmittable, U = U). However, the science of treatment-as-prevention (TasP) may not be widely understood by people with and without HIV who could benefit from this information. We systematically reviewed the global literature on knowledge and attitudes related to TasP and interventions providing TasP or U = U information. We included studies of providers, patients, and communities from all regions of the world, pub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
65
1
12

Year Published

2021
2021
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 83 publications
(100 citation statements)
references
References 87 publications
(126 reference statements)
6
65
1
12
Order By: Relevance
“…A recent systematic review found that 31 studies measured TasP knowledge globally, from 2008 to 2020. 13 However, just two were quantitative studies of community-based samples in sub-Saharan Africa. In 2013, 65% of survey participants in rural Malawi perceived that ART had no impact on transmission risk.…”
Section: Behaviourmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent systematic review found that 31 studies measured TasP knowledge globally, from 2008 to 2020. 13 However, just two were quantitative studies of community-based samples in sub-Saharan Africa. In 2013, 65% of survey participants in rural Malawi perceived that ART had no impact on transmission risk.…”
Section: Behaviourmentioning
confidence: 99%
“…[9][10][11][12] However, data from sub-Saharan Africa are scarce. 13 Evidence from South Africa, Zambia and Uganda suggest low familiarity with TasP in rural areas. [14][15][16] However, information may have diffused faster in urban areas, among young adults, and among those with access to secondaryschool HIV education and university health services.…”
Section: Introductionmentioning
confidence: 99%
“…The HIV prevention, treatment and care landscape has nevertheless evolved, e.g. immediate ART initiation (fewer HIV-related complications), new more well-tolerated classes of ART, and campaigns targeting HIV-stigma 15 , 16 , potentially easing the burden of depressive disorder in PLWH. Thus, we aimed to (1) estimate the prevalence of depressive disorder in PLWH, (2) identify factors associated with depressive disorder in PLWH, and (3) understand which factors are associated with an excess of depressive disorder in PLWH compared to the GP.…”
Section: Introductionmentioning
confidence: 99%
“…Yet, considerable work remains to use this message widely towards ending stigma and thus advancing health equity for PLHIV. In sub-Saharan Africa, for instance U = U awareness remains very low and varies by HIV status [3]. Even in areas with higher levels of U = U awareness in some communities (such as in Europe, Asia, the Americas and Oceania), misinformation abounds regarding its effectiveness [3], limiting full realization of this powerful health strategy [4].…”
mentioning
confidence: 99%